Coleção Ensino de Ciências na Escola: um repositório digital com apoio pedagógico para o ensino e a formação - SANTOS, Gisele Damasceno dos (2023)
Digital repositories are important tools for digital and free access to materials with the potential to contribute positively to teachers´ practices. This research aims to describe and analyze the construction of a digital repository to host the collection “Science Teaching in School” with 12 digital catalogs of educational products (EP). The methodology is based on two phases: the first comprised a bibliography search in 36 Professional Masters Programs in Science Teaching, between 2010 and 2019, to identify and systematize the EP. The second phase has two parallel steps: (i) the publishing and layout of digital catalogs through App Canva®; (ii) the building of a digital repository. The results have originated educational materials that can be affordable innovation products, which aim for the improvement of Biology and Science teaching, as well as the fortification of initial training and continued education teachers.